Beginning Laravel : build websites with Laravel 5.8 - Sinha, Sanjib (Apress, 2019)
Develop cutting-edge websites and applications using the new features of Laravel 5.8. This book starts with an introduction to Laravel and takes a glance at its newly introduced features. Moving on to setting up your development environment, you will learn how the composer works. In addition to this, you will be introduced to Valet, Homestead, Virtual Box, Vagrant, and Forge in Laravel. With this foundation, you will be ready to get started writing your first Laravel apps. To do so, you will learn to manage routes and controllers and how the Blade template works. Moving on to models, you will work with route model binding and get to know the relationship between models, databases, and Eloquent. Along the way you will define methods on your Eloquent model classes using different types of relationships. Shifting focus to handling user data, you will see how redirect methods work. You will also get to know the inner workings of requests and responses. Continuing the data theme, Beginning Laravel covers basic and grouped artisan commands and how to handle databases with Tinker. By being able to handle data effectively, your applications will come alive for your users, giving them the functionality they need. The last section of the book handles core concepts such as sending emails, alerting users via notifications, and implementing SOLID design principles. You will see how to decouple your application classes by using events and listeners. You will: Protect your app with authentication and authorization Build a complex relationship between entities using Eloquent models Take advantage of containers and facades Use the mail template Create and configure events Work with Laravel Passport Deploy API authentication Discover new Laravel 5.8 features such as dump server and email verification.